Non-signatory States in International Refugee Law - Janmyr, Maja,; Kazmi, Arjumand Bano,; Skribeland, Özlem Gürakar, (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
Non-signatory States in International Refugee Law explores the relationship between the international refugee regime and states that are non-signatory to the 1951 Convention relating to the Status of Refugees and its 1967 Protocol. The collection examines how these instruments play a central role in shaping responses to refugees. It unpacks the ways in which international refugee law manifests itself in non-signatory states and how those states in turn contribute to its development. The contributions are legally informed and richly contextualized, providing empirical, conceptual, critical and historical insights into how and why the Refugee Convention matters globally.